Effect of the plastic pollutant bisphenol A on the biology of aquatic organisms: A meta‐analysis. (21st May 2020) - Wu, Nicholas C.; Seebacher, Frank
Abstract: Plastic pollution is a global environmental concern. In particular, the endocrine‐disrupting chemical bisphenol A (BPA) is nearly ubiquitous in aquatic environments globally, and it continues to be produced and released into the environment in large quantities. BPA disrupts hormone signalling and can thereby have far‐reaching physiological and ecological consequences. However, it is not clear whether BPA has consistent effects across biological traits and phylogenetic groups. Hence, the aim of this study was to establish the current state of knowledge of the effect of BPA in aquatic organisms. We show that overall BPA exposure affected aquatic organisms negatively. It increased abnormalities, altered behaviour and had negative effects on the cardiovascular system, development, growth and survival. Early life stages were the most sensitive to BPA exposure in invertebrates and vertebrates, and invertebrates and amphibians seem to be particularly affected. These data provide a context for management efforts in the face of increasing plastic pollution. However, data availability is highly biased with respect to taxonomic groups and traits studies, and in the geographical distribution of sample collection. The latter is the case for both measurements of the biological responses and assessing pollution levels in water ways. Future research effort should be directed towards biological systems, such as studying endocrine disruption directly, and geographical areas (particularly in Africa and Asia) which we identify to be currently undersampled. Abstract : Plastic pollution is a global environmental concern. In particular, bisphenol A (BPA) is nearly ubiquitous in all aquatic environments. BPA disrupts hormone signalling and can thereby have far‐reaching physiological and ecological consequences. This study aimed to establish the current state‐of‐knowledge on global environmental BPA levels and their effects on aquatic organisms. We show that BPA exposure affected a myriad of biological functions in aquatic organisms. Early life stages were the most sensitive to BPA exposure, and invertebrates and amphibians seem to be particularly affected. Our meta‐analysis identified important gaps in knowledge and we suggest future research directions.